(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Stephen King’s "Dead Zone" is enriched with humanistic ideas, in which the author works not on the basis of rumors and speculation in society, but on the basis of scientifically based facts, which allows him to take his work seriously. This article is about portraying the ideas of goodness and humanity expressed in the play, and about the features of these ideas when creating a fantastic work.